Retirement plan among employees in SAJ Ranhill Sdn. Bhd. Segamat, Johor / Nurhamizah Adilah Abdul Halim - Abdul Halim, Nurhamizah Adilah (Faculty of Business and Management, 2018)
In this era, life expectancy has improved globally. One of the reasons is because the emerging of technology advance in medical that helps people living longer. Because of that, people nowadays are living longer in retirement. It is agreeable that by extending the retirement age can solve the financial issue. However, by solving this problem it will lead to another problem where the opportunity for the young generation to enter the workforce will be decrease. Furthermore, by increasing the retirement age it will also affect other employees’ career development where they have to wait longer to be promoted. This study was conducted on SAJ Ranhill Sdn. Bhd. Segamat, Johor employees. This research has three objectives. The first objective is to identify the relationship between economic condition and retirement plan of SAJ Ranhill Sdn. Bhd. Segamat, Johor employees. Next, the second objective is to examine the relationship between health condition and retirement plan of SAJ Ranhill Sdn. Bhd. Segamat, Johor employees. Lastly, the third objective is to investigate the relationship between working condition and retirement plan of SAJ Ranhill Sdn. Bhd. Segamat, Johor employees. In addition, this research used non probability sampling which is convenient sampling. In this study, questionnaire was used because it is less expensive and time consuming. Based on the findings, it can be indicates that economic condition and working condition have a significant relationship with retirement plan of SAJ Ranhill Sdn. Bhd. Segamat, Johor employees. However, health condition was found not to have a significant relationship with the retirement plan of the employees.